RELATIONSHIP BETWEEN QUALITY OF CARE OF YOUNG MOTHERS AND SOCIAL-EMOTIONAL DEVELOPMENT IN PRESCHOOL CHILDREN - Atik Aryani; Sri Warsini; Fitri Haryanti (Belitung Raya Foundation, Indonesia, 2018)
Background: Social-emotional development in preschooler children is an important component in child development, as it becomes the foundation in preparing children for confidence, empathy and intellect, building trust, and being able to use language in communication and connect with others. One of the factors that affect children's emotional social development is the quality of mother's care. Children of young mothers have risks in emotional and intellectual social problems in children. Objective: The purpose of the study was to determine the relationship of quality care of young mothers with social-emotional development in preschool children in the working area of the Health Center of Kemalang, Klaten Regency, Indonesia. Methods: This was a correlational analytic research with cross sectional design. The sample of the study was 124 young mothers with preschool children selected using consecutive sampling technique. The study was conducted from July to August 2017 at six kindergarten schools in the working area of the Health Center of Kemalang, Klaten Regency. Data were collected using parent behavior questionnaire and stage social-emotional instrument. Data were analyzed using chi square test. Results: Findings showed that 58.1% of young mothers had good quality of care, and 55.6% of preschoolers were at risk of developing emotional social development problems. There was a significant correlation between the quality of care of young mothers with social-emotional development in preschool children (p-value <0.05). Conclusion: There was a correlation between the quality of care of young mothers with social-emotional development in preschool children.